The 2013 Curriculum Based Syllabus For Senior High School’s English Extracurricular Program - Mustolih, Masrur; Hermayawati, Hermayawati (LPPM Universitas Mercu Buana Yogyakarta, 2015)
The study aimed at designing syllabus for English extracurricular in SMAN 1 Seyegan based on the 2013 Curriculum. This was Research and Development (R&D) study using ADDIE model. There were five stages in conducting the research; (1) Analysis; (2) Design; (3) Development; (4) Implementation; (5) Evaluation. This study involved 15 students of ten graders who registered to English extracurricular program. To gain the Needs Analysis (NA), the researcher used observation, questionnaire, interview, and documentation. This study found a 2013 curriculum based syllabus using is matrix format. It consists of 21 units for two semesters; ‘Introduction’, ‘Greeting, meeting and parting’, ‘Self-Introduction’, ‘Compliment, ‘Caring’, ‘Past Time’, ‘Descriptive Text’, ‘Announcement Text’, ‘Introduction to Public Speaking’ ‘Speech’, ‘Storytelling’, ‘Indonesian Culture’, ‘Foreign Culture’, ‘Study Abroad’, ‘Writing a letter, ‘Debate Contest’, ‘Australasian Debate Style’, ‘British Debate Style’, ‘Vacation ’and 2 units for semester exam. It was appropriate with the 2013 Curriculum based on (1) an expert judgment from Mercu Buana University of Yogyakarta; (2) theFocus Group Discussion from English teacher and school principal of SMA N 1Seyegan; (3) the results of pre-test and post-test in two cycles which showed there was improvement. Based on the findings above, it is recommended for the further researcher to develop the designed syllabus into module for English extracurricular.